Personality Profile Differences Between Prisoners and Non-Prisoners Using the Personality Inventory for DSM-5 (PID-5) - Widhi Adhiatma; Magdalena S. Halim (ANIMA Indonesian Psychological Journal, 2016)
Prison provides correctional function for prisoners. There are some factors needed to be considered to enable the correctional process work optimally, one of them is the personality of prisoners. We need to consider this because there are different kinds of prisoners with different criminal backgrounds. This study aimed to identify the personality profiles of prisoners, including violent offenders, non-violent offenders and drug offenders, using the Indonesian version of Personality Inventory for DSM-5 (PID-5). We compared the personality profiles of the prisoners’ groups with the non-prisoner’s group in order to have more accurate personality profiles. The samples consisted of groups of violent offenders (n = 96, mean age = 27.99 years old), non-violent offenders (n = 79, mean age = 35.55 years old), drug offenders (n = 180, mean age = 32.90 years old), and non-prisoners (n = 245, mean age = 23.31 years old). Analyses using a series of One-Way ANOVA at the level of domains and facets of personality showed differences in the personality profiles of the three groups of prisoners and non-prisoner. In comparison to the non-prisoner group, the drug offender group was found having the largest number of differences in the personality profiles, whilst the non-violent offender group had the least number of personality profile differences.